The effect of natural rainfall on salt leaching under watertable management. (26th April 2018) - Li, Shan; Luo, Wan; Jia, Zhonghua; Tang, Shuangcheng; Chen, Cheng
Abstract: Natural rainfall may produce effective leaching in some salt‐impacted irrigation areas; but the variable nature of rainfall often makes it difficult to assess the actual leaching effect of rainfall under different irrigation and drainage management. With a proposed analytical model that considers watertable management and crop use of shallow groundwater, this paper presents a case study that examined salt leaching effect of the natural rainfall in a semiarid irrigation area; the salt balance calculation was based on the daily watertable depth predicted by the DRAINMOD model using 55‐year weather data. The results showed that salt leaching effect of the natural rainfall depended on the control depth of field watertable through drainage system, crop use of shallow groundwater, and supplemental irrigation. For the salt tolerant crop—cotton, with the field watertable depth controlled at 1.5 m and the annual supplemental irrigation as 80 mm, the predicted average root zone salinity did not exceed the cotton tolerance level (4.92 g/L) in the simulation period. When the watertable depth was controlled at 1.2 m, due to increased shallow groundwater use, the predicted average root zone salinity was below the cotton tolerance level in 80% years with annual irrigation of 100 mm; and the predicted root zone salinity was below the cotton tolerance level in 96.4% years with annual irrigation of 150 mm. To achieve higher water use efficiency in semiarid irrigation area with saline shallow groundwater, proper watertable management is necessary to make use of the natural rainfall for salt leaching and shallow groundwater for temporary drought relief.